Monitoring to graduates from the Industrial Management School of Universidad Pedagógica y Tecnológica de Colombia - Báez Roa, María del Pilar (Universidad Pedagógica y Tecnológica de Colombia, 2010)
This paper aims to track the graduates of Industrial Administration, to assist in the process of quality improvement and accreditation of the program. Obtaining information regarding their opinion about the training, the weaknesses, strengths and relevance to the environment from the use of surveys and interviews with graduates. In this way, identify needs that require special emphasis, aspects to be taken into account for the restructuring of curriculum and promoting opportunities for continuing education. The quantitative methodology is applied to the graduates. The main results obtained with this investigation are: to strengthen the areas of administration and production, develop skills and ethical values, responsibility and decision making, promote the implementation of business practices, develop activities possessions to the graduate level national reform including the curricular subjects such as entrepreneurship and socio-humanistic, offer specializations in the areas of administration, production, talent management and finance, creating an employment, strengthening the link-graduate college and update data base of graduates.